Effectiveness of Flipped Classroom Method in Improving Students Academic Skills: Scoping Review - Ernawati, Ernawati; Susanti, Ari Indra (Jurnal Locus Penelitian dan Pengabdian, 2026)
The quality of students' academic skills is one of the important indicators in the success of the higher education process, but traditional learning methods are often less effective in encouraging active student involvement. The purpose of this study is to analyze the effectiveness of flipped classroom method in improving students academic skills: scoping review. The research method used is a scoping review with databases from PubMed, Sage Journals, and ScienceDirect. The results obtained were 10 articles that were reviewed, with the main themes being the effectiveness of the flipped classroom method, student involvement in learning, student perceptions of the flipped classroom learning method, and challenges and obstacles in implementing this learning method. The research findings indicate that academic skills—which include critical thinking skills, analytical skills, creative skills, communication skills, and collaboration skills—significantly improved. Students feel more prepared when taking part in learning because they have previously studied the material to be discussed. The application of this learning method is highly recommended for educational institutions to improve the quality of students and educational institutions.